Drought and flooding have distinct effects on herbivore‐induced responses and resistance in Solanum dulcamara. (6th April 2016) - Nguyen, Duy; D'Agostino, Nunzio; Tytgat, Tom O. G.; Sun, Pulu; Lortzing, Tobias; Visser, Eric J. W.; Cristescu, Simona M.; Steppuhn, Anke; Mariani, Celestina; van Dam, Nicole M.; Rieu, Ivo
Abstract: In the field, biotic and abiotic stresses frequently co‐occur. As a consequence, common molecular signalling pathways governing adaptive responses to individual stresses can interact, resulting in compromised phenotypes. How plant signalling pathways interact under combined stresses is poorly understood. To assess this, we studied the consequence of drought and soil flooding on resistance of Solanum dulcamara to Spodoptera exigua and their effects on hormonal and transcriptomic profiles. The results showed that S . exigua larvae performed less well on drought‐stressed plants than on well‐watered and flooded plants. Both drought and insect feeding increased abscisic acid and jasmonic acid (JA) levels, whereas flooding did not induce JA accumulation. RNA sequencing analyses corroborated this pattern: drought and herbivory induced many biological processes that were repressed by flooding. When applied in combination, drought and herbivory had an additive effect on specific processes involved in secondary metabolism and defence responses, including protease inhibitor activity. In conclusion, drought and flooding have distinct effects on herbivore‐induced responses and resistance. Especially, the interaction between abscisic acid and JA signalling may be important to optimize plant responses to combined drought and insect herbivory, making drought‐stressed plants more resistant to insects than well‐watered and flooded plants. Abstract : This study investigated the molecular interactions of plant responses to abiotic stresses, including drought and flooding, and herbivore‐induced responses. Using the wild tomato relative Solanum dulcamara and the generalist caterpillar Spodoptera exigua, we demonstrated that drought enhanced herbivore‐induced hormonal and transcriptional responses, whereas they were repressed by flooding. Herbivore performance and protease inhibitor assays confirmed the additive effects of drought and herbivory on plant resistance. Especially, the interaction between abscisic acid and jasmonic acid signalling was found to be important in making drought‐stressed plants more resistant to insects than well‐watered and flooded plants. These novel findings contribute to a better understanding of the complex physiological mechanisms underlying multiple stress responses as they occur in natural and agricultural ecosystems.